Because I say so thinking Christianly about discipline and punishment - Hill, Brian (Bondi Junction, NSW Australian Teachers' Christian Fellowship, 1989)
Includes bibliographical references.
Donated by the Australian Teachers' Christian Fellowship, residents of Emmaus Bible College, March 2004.
Keywords: Teaching -- discipline